A review of blockchain technology implementation in shipping industry - Jović, Marija, inženjerka pomorstva (Array, 2019)
This article presents a comprehensive review of the current and rising trends of blockchain technology usage in shipping industry. The definition and features of blockchain technology are provided, as well as the potential usage of blockchain technology in various areas (financial services, Internet of Things, medicine, government, etc.), in order to better understand its complexity and application. Furthermore, the major challenges of blockchain technology are shown, and the most prominent examples of blockchain applications in shipping industry are provided. The application and advantages of blockchain technology in seaports are demonstrated through several examples.